Gestational Oxidative Stress and OGTT: Are Pregnant Women’s Fears Justified? - Genc SO; Erdal H (Diabetes, Metabolic Syndrome and Obesity)
Serife Ozlem Genc,1 Huseyin Erdal2 1Department of Obstetrics and Gynecology, Sivas Cumhuriyet University Faculty of Medicine, Sivas, Turkey; 2Department of Medical Genetics, Aksaray University Faculty of Medicine, Aksaray, TurkeyCorrespondence: Serife Ozlem Genc, Sivas Cumhuriyet University Faculty of Medicine Hospital, Department of Obstetrics and Gynecology, Block: B, Floor: 1, No: 10, Sivas, 58140, Turkey, Tel +90 543 456 56 24, Email drserifeozlemgenc@gmail.comPurpose: Pregnancy induces significant metabolic, immunological, and endocrinological changes to support fetal growth. The 75-gram oral glucose tolerance test (OGTT) is standard for gestational diabetes screening, but concerns exist about its potential to induce oxidative stress, affecting both maternal and fetal health. The aim of the study is examining changes in oxidative stress markers and thiol/disulfide homeostasis in pregnant women to evaluate these concerns.Patients and Methods: Thirty pregnant women undergoing gestational diabetes screening between the 24th and 28th weeks participated. Blood samples were collected at 0, 60, and 120 minutes as part of the OGTT protocol. Oxidative stress markers were analyzed only in samples from 0 and 120 minutes, while the 60-minute sample was used solely for glucose measurement.Results: Results showed a significant increase in TOS (p = 0.008) and OSI (p = 0.035) post-OGTT, indicating an acute oxidative stress response. Thiol and disulfide levels showed non-significant changes, suggesting that antioxidant mechanisms were largely unaffected.Conclusion: Further research is necessary to explore the long-term implications of these findings and develop strategies to mitigate oxidative stress during pregnancy. This study provides insights into the acute oxidative stress response caused by OGTT in pregnant women. Although the OGTT induces oxidative stress, it does not significantly disrupt the body’s antioxidant capacity in the short term. These results highlight the need for more research to understand the effects of heightened oxidative stress on maternal and fetal health.Keywords: antioxidant status, oral glucose tolerance test, oxidative stress, pregnancy, thiol disulfide